SARS-CoV2-mediated suppression of NRF2-signaling reveals potent antiviral and anti-inflammatory activity of 4-octyl-itaconate and dimethyl fumarate - David Olagnier (Nature Portfolio, 2020)
Viral infections usually cause disease through direct cytopathogenic effects and excessive inflammatory responses. Here, Olagnier et al. show that two NRF2 agonists, 4-OI and DMF, possess broad IFN-independent antiviral activity and decrease host inflammatory response to SARS-CoV-2 infection.